Pyrolysis of Biomass Impregnated With Ammonium Dihydrogen Phosphate for Polygeneration of Phenol and Supercapacitor Electrode Material - Li, Kai; Wang, Bo; Bolatibieke, Dana; Nan, Dong-hong; Lu, Qiang (Frontiers in Chemistry, 2020)
A novel method was proposed for polygeneration of phenol and supercapacitor electrode material from pyrolysis of biomass impregnated with ammonium dihydrogen phosphate (NH4H2PO4). The pyrolysis experiments were executed to demonstrate the product distributions under different NH4H2PO4-to-poplar (PA-to-PL) ratios and pyrolysis temperatures in a lab-scale device. The results revealed that the phenol yield attained its optimal value of 4.57 wt% with a satisfactory selectivity of 20.09% at 500°C under PA-to-PL ratio of 5. The pyrolytic solid product obtained at this condition was then subjected to high temperature activation directly without additional activators to prepare N and P co-doped activated carbon (NPAC) as supercapacitor. The physicochemical analysis of NPAC showed that the N and P contents in NPAC reached 3.75 wt% and 3.65 wt%, respectively. The electrochemical experiments executed in a three-electrode system indicated that the NPAC exhibited promising electrochemical performance with a satisfactory capacitance of 181.3 F g -1 at 1 A g -1 .